Efficacy and safety of an algorithm using C-reactive protein to guide antibiotic therapy applied through a digital clinical decision support system: a study protocol for a randomised controlled clinical trial - Vandack Nobre; Pedro R Povoa; Vitoria Moura Leite Rabelo Rezende; Isabela Nascimento Borges; Cecilia Gomez Ravetti; Renan Pedra De Souza; Paula Frizera Vassalo; Ana Clara de Paula Caldas; Felipe Rodrigues Gatto; Getulio Hideyoshi Okamura; Raquel Lopes de Brito Lacerda (BMJ Open)
Introduction The escalating resistance of microorganisms to antimicrobials poses a significant public health threat. Strategies that use biomarkers to guide antimicrobial therapy—most notably Procalcitonin (PCT) and C-reactive protein (CRP)—show promise in safely reducing patient antibiotic exposure. While CRP is less studied, it offers advantages such as lower cost and broader availability compared with PCT.Methods and analysis This randomised clinical trial aims to evaluate a novel algorithm for non-critically ill adult patients. The algorithm incorporates key clinical variables and CRP behaviour. It will be applied through a mobile application as a digital clinical decision support system. The primary goal will be to assess the algorithm’s effectiveness in reducing treatment duration compared with standard care based on current guidelines, while ensuring patient safety by monitoring the occurrence of adverse events.Ethics and dissemination Only patients who agree to participate in the study after reading the informed consent form will be included. This project was submitted for consideration to the Research Ethics Committee of the Federal University of Minas Gerais (COEP-UFMG) and received approval (Approval Number: 5.905.290). Collection of clinical and laboratory data from 200 patients is expected, extracted from electronic medical records and laboratory systems, along with serum samples stored for potential future analyses. Data will be preserved using the Research Electronic Data Capture platform, and serum samples will be stored in a regulated biorepository at UFMG. Access will be controlled via credentials, with privacy protections and anonymisation prior to sharing, which will occur during scientific publications.Trial registration number This trial was registered on ClinicalTrials.gov (NCT05841875) and was last updated on 5 December 2024 at 12:49.